2016
DOI: 10.1097/psy.0000000000000330
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Aftermath of Terror: Fundamental Outcomes, Methodological Choices, and Future Directions

Abstract: Acts of terrorism are becoming increasingly common throughout the world. These events represent a significant public health concern given the associated health consequences. Although it is clear that terrorist attacks have mental and physical health sequelae, the exact nature and prevalence of these consequences are unclear. Epidemiological research can play an important role in better understanding the mental and physical impact of terrorist attacks. In this editorial, we highlight recent epidemiological rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
(15 reference statements)
0
0
0
Order By: Relevance
“…Another study found increases in hospitalizations for schizophrenia and psychosis in Norway after the 2011 Oslo and Utøya Island terrorist attack (Strand, Mukamal, Halasz, Vatten, & Janszky, 2016; as cited in Gradus, Marx, & Sloan, 2016). The researchers also found increases in hospitalization for suicide, acute myocardial infarctions, births, and preterm births.…”
Section: Effects Of Disasters On Hospitalization For Schizophreniamentioning
confidence: 91%
“…Another study found increases in hospitalizations for schizophrenia and psychosis in Norway after the 2011 Oslo and Utøya Island terrorist attack (Strand, Mukamal, Halasz, Vatten, & Janszky, 2016; as cited in Gradus, Marx, & Sloan, 2016). The researchers also found increases in hospitalization for suicide, acute myocardial infarctions, births, and preterm births.…”
Section: Effects Of Disasters On Hospitalization For Schizophreniamentioning
confidence: 91%